PENGARUH CITRA MEREK DAN PERSEPSI HARGA TERHADAP LOYALITAS MELALUI KEPUASAN PELANGGAN DIHOTEL MEGA ANGGREK JAKARTA - Ahmad Rofik; Rivera Silitonga (LPPM Universitas Asa Indonesia, 2022)
This study aims to determine the influence of brand image, and price perception on loyalty through customer satisfaction at Hotel Mega Anggrek Jakarta.The population in this study are consumers from Hotel Mega Anggrek Jakarta using the purposive sampling method with a total sample of 197 respondents with data collection through a questionnaire with a likert scale of 5 (five) alternatives that have been tested for validity and reliability. Path Analysis and sobel test data analysis techniques. With the results of the research, brand image and quality variables have a significant influence on customer satisfaction, brand image variables, product quality and customer satisfaction have a significant influence on loyalty, and customer satisfaction variables have a significant influence mediating the influence of brand image and price perception on loyalty.